2015
DOI: 10.1111/eva.12263
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of Puumala hantavirus associated with its rodent host, Myodes glareolus

Abstract: Many viruses significantly impact human and animal health. Understanding the population dynamics of these viruses and their hosts can provide important insights for epidemiology and virus evolution. Puumala virus (PUUV) is a European hantavirus that may cause regional outbreaks of hemorrhagic fever with renal syndrome in humans. Here, we analyzed the spatiotemporal dynamics of PUUV circulating in local populations of its rodent reservoir host, the bank vole (Myodes glareolus) during eight years. Phylogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 83 publications
12
52
0
Order By: Relevance
“…Puumala orthohantavirus RNA detection rate in the bank vole varied considerably with a peak at about 60% in the south and parts of the north‐west, almost reaching values observed during previous PUUV outbreaks. For instance, PUUV RNA detection rate in district Osnabrück in spring of previous outbreak years was 86% (2010) and 75% (2012) (Weber de Melo et al, ). However, in other regions in the north‐west and in central Germany PUUV RNA detection rate was low and did not reach prevalence values reported for previous outbreaks of PUUV in Germany (Reil et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Puumala orthohantavirus RNA detection rate in the bank vole varied considerably with a peak at about 60% in the south and parts of the north‐west, almost reaching values observed during previous PUUV outbreaks. For instance, PUUV RNA detection rate in district Osnabrück in spring of previous outbreak years was 86% (2010) and 75% (2012) (Weber de Melo et al, ). However, in other regions in the north‐west and in central Germany PUUV RNA detection rate was low and did not reach prevalence values reported for previous outbreaks of PUUV in Germany (Reil et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…These public health measures of monitoring local bank voles for PUUV strains ( 4 ) should be expanded to evaluate for further northeastern expansion.…”
Section: Resultsmentioning
confidence: 99%
“…Including results of previously published studies ( 3 , 4 , 7 ), PUUV seroprevalence in the endemic regions showed an average of 23.9% and varied between 4.6% and 66.7% (Technical Appendix Table). According to the serologic and RT-PCR data, a PUUV-endemic region can be identified spanning the western and southern parts of Germany (Figure 1, panel A, below the dotted red line).…”
Section: The Studymentioning
confidence: 98%
See 1 more Smart Citation
“…; Weber de Melo et al . ). While hantaviruses were shown to be subjected to genetic drift and reassortment at a local scale, part of the variation was transient and balancing selection, limiting amino acid changes, was also noticed with other hantaviruses (Razzauti et al .…”
Section: Discussionmentioning
confidence: 97%